X-Innovation: Re-Inventing Innovation Again and Again - Gaglio, Gérald; Godin, Benoît; Pfotenhauer, Sebastian (NOvation — Critical Studies of Innovation, 2019)
Innovation is an old word, of Greek origin, that came into the Latin vocabulary in the early Middle Age and into our everyday vocabulary with the Reformation. However, it is only during the second half of the twentieth century that innovation became a fashionable concept and turned into a buzzword. It gave rise to a plethora of terms like technological innovation, organizational innovation, industrial innovation and, more recently, social innovation, open innovation, sustainable innovation, responsible innovation. We may call these terms X-innovation. In this way, X-innovation is the latest step to give sense to a century-old process of enlargement of the concept of innovation. Over the last five centuries, innovation enlarged its meaning from the religious to the political to the social to the economical. X-innovation is the more recent such enlargement. It Is the continuation, under new terms, of the contestation of technological innovation as the dominant discourse of the twentieth century. How can we make sense of this semantic extension? Why do these terms come into being? What drives people to coin new terms? What effects do the terms have on thought, on culture and scholarship and on policy and politics? Which forms of contestation and appropriation ensue around certain X-innovations? How do they shape, and are shaped by, broader social trends? How to they relate to questions of power and inclusion?